Perceptions of vaccine preventable diseases in Australian healthcare: focus on pertussis - Julianne Bayliss; Roshnee Randhawa; Kyu-Bin Oh; Walid Kandeil; Victoria A. Jenkins; Elisa Turriani; Michael Nissen (Taylor & Francis Group, 2021)
Adult vaccination in Australia is suboptimal. For instance, as few as one in nine people have received a pertussis vaccine in adolescence or adulthood, despite increasing disease burden and evidence of a positive correlation between older age and hospitalization rates. The objectives of this study were to describe general practitioners' (GPs) and adult consumers' knowledge and attitudes toward adult vaccination, with an emphasis on pertussis. Australian GPs and consumers were recruited in two nationally representative online surveys repeated annually between 2014 and 2018. Vaccination discussions occurred in a minority of adult/GP encounters. Pertussis was among the five most frequently identified vaccine preventable diseases but was unlikely to be proactively discussed with adults not in contact with young children. Among consumers, only one in three recalled ever receiving a pertussis vaccination. GPs are a strong predictor of adults receiving a pertussis vaccine. Possible factors contributing to low uptake are misconceptions around pertussis disease, vaccination requirements and lack of GP recommendation for adult vaccination. GPs have a key role to play in increasing adult vaccination coverage with their recommendation.